2018
DOI: 10.1017/s1355770x18000098
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of coal-fired power plants in China

Abstract: Coal has fueled China's rapid growth in recent decades, but it also severely pollutes the air and causes many health issues. The magnitude of the health damage caused by air pollution depends on the location of emission sources. In this paper, we look into the spatial distribution of coal-fired power plants, which are the major emission sources in China, and investigate the determining factors behind the distribution. We find that the driving factors are economic development and expansion of electricity grid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The reason behind the differences in the inter-regional inefficiency values among the regions could be the economic level of the regions. Xie et al [30] stated that economic growth is one of the driving factors of new construction of coal-fired thermal power plants in China. Since the eastern region is the most developed area in China, the growing electricity demand in the east induced the new construction of large power plants with advanced technology in that region, which may contribute to lowering the inter-regional inefficiency of the LARGE group in that region.…”
Section: Datamentioning
confidence: 99%
“…The reason behind the differences in the inter-regional inefficiency values among the regions could be the economic level of the regions. Xie et al [30] stated that economic growth is one of the driving factors of new construction of coal-fired thermal power plants in China. Since the eastern region is the most developed area in China, the growing electricity demand in the east induced the new construction of large power plants with advanced technology in that region, which may contribute to lowering the inter-regional inefficiency of the LARGE group in that region.…”
Section: Datamentioning
confidence: 99%
“…Regional heterogeneity in economic development is one of the primary reasons for the remarkably lower inter-regional factor in the eastern and central regions compared to the west and northeast. Xie et al [47] revealed that economic development is a driving force for the construction of CTPPs in China. The eastern and central Chinese regions are more economically developed; thus, the introduction of power plants with leading-edge Regional heterogeneity in economic development is one of the primary reasons for the remarkably lower inter-regional factor in the eastern and central regions compared to the west and northeast.…”
Section: Metafrontier Dea Decomposition Analysismentioning
confidence: 99%
“…The eastern and central Chinese regions are more economically developed; thus, the introduction of power plants with leading-edge Regional heterogeneity in economic development is one of the primary reasons for the remarkably lower inter-regional factor in the eastern and central regions compared to the west and northeast. Xie et al [47] revealed that economic development is a driving force for the construction of CTPPs in China. The eastern and central Chinese regions are more economically developed; thus, the introduction of power plants with leading-edge technology has historically been promoted, contributing to the lower inter-regional factor in these areas.…”
Section: Metafrontier Dea Decomposition Analysismentioning
confidence: 99%
“…Spatially variable scale factors of 2.1-6.8 are applied to seven grid squares for the MEIC SO2 emissions. These are concentrated in Shanxi province west of BTH, a region with large coal-fired power plants (Xie et al, 2018). These grids account for the majority of the domain average 42% underestimate in modelled SO2 concentrations.…”
Section: Bth Air Pollution and Emissions For The Year Preceding Emission Controlsmentioning
confidence: 99%